Joanna's miracle - Armstrong, William H. (William Howard), 1914-1999. (Nashville : Broadman Press, 1977)
After hearing about the miracles performed by the young carpenter from Nazareth, a fourteen-year-old cripple sets out on her own to find Him.
Keywords: Jesus Christ -- Fiction; People with disabilities -- Fiction